In the robes of Christ. (August 2016) - Howell, Eric
A pastoral sabbatical season is a significant commitment for both the pastor and the congregation. Accordingly, the good made possible by sabbaticals extends far beyond the few months during which the congregation absorbs the pastor's typical ministerial responsibilities. Done well, these seasons are vital for pastoral longevity in just the way that sabbaticals give pastors the space and opportunity to reflect on their own vocational journeys and identities. This article reflects on one pastor's sabbatical experience at Taizé, in the steps of St. Francis, and at a monastery while framing an evolving vocational identity through three stages in an adult life. It also reflects on George Herbert's poem "Aaron, " in which Herbert traces the pastoral identity from its paucity in the face of the ideal image of priestly ministry toward Christ's infusion of ministerial grace. He "lives in me" declares Herbert finally. This article also introduces a surfing monk, whose (apparently) grudging submission to authority is both the challenge and beauty of the pastoral vocation with the local church. Following a personal experience and George Herbert, the author employs "robes" as the image of pastoral vocational identity.